Conservation strategies for endangered animal species (Zoological Records and Reviews, 2024)
Selecting among available conservation strategies for endangered animal species requires rigorous evaluation ofintervention effectiveness, cost-efficiency, and long-term viability under projected future conditions. This study evaluatesthe outcomes of six conservation strategies -- in situ habitat protection, habitat restoration, ex situ captive breeding withreintroduction, legal protection enforcement, community-based conservation, and species-specific research programmes-- applied to sixteen Critically Endangered (CR) or Endangered (EN) vertebrate species across Austria, Germany, andItaly between 2005 and 2023. Strategy outcomes were quantified using population trend indices derived from long-termmonitoring data (n = 18,284 individual records), population viability analysis (PVA) projections, and cost-effectivenessratios (species-years of population stability per 10,000 EUR invested). In situ habitat protection combined with habitatrestoration achieved the highest mean population trend improvement (+2.8% per year; 95% CI: +1.9 to +3.7%) and thehighest cost-effectiveness ratio (4.8 species-years / EUR 10,000) across the sixteen species. Ex situ captive breedingwith reintroduction achieved the highest single-species absolute recovery (European bison Bison bonasus: populationincrease +284 individuals over 18 years) but the lowest cost-effectiveness ratio (0.8 species-years / EUR 10,000).Community-based conservation was the most cost-effective strategy for species in human-dominated landscapes (meanratio 3.6 species-years / EUR 10,000). PVA projections under current strategy conditions show that eleven of sixteenspecies have > 90% probability of persistence over 100 years, while five remain at high extinction risk requiring strategyintensification. These findings provide an evidence-based framework for strategy selection and resource allocation innational species recovery plans under EU Habitats Directive reporting obligations.
Keywords: central Europe; species recovery; EU Habitats Directive; community-based conservation; cost-effectiveness; habitat restoration; captive breeding; population viability analysis; endangered species; conservation strategies